Manual of good beekeeping practices in artificial feeding of bees: a contribution to the quality of Argentine honey. - Dini, Cecilia Beatriz (compiladora); García, Norberto (compilador) (Convenio INTA-Nexco, 2023)
It is part of the Beekeeping Program of INTA (PROAPI), and INTA-NEXCO S.A. Agreement.